Ectopic thoracic kidney in a child presenting with recurrent cough: a case report and review of literature. Issue 3 (July 2017) - Sinha, Amit K.; Vaghela, Maheshkumar M.; Kumar, Bindey; Kumar, Prem; Neha, Neeti
Abstract : Ectopic thoracic kidney is a rare clinical entity in pediatric patients. It is usually an incidental finding on evaluation of patients with recurrent cough or mediastinal mass. Its clinical course is benign. We are presenting a case of right ectopic intrathoracic kidney diagnosed incidentally on contrast-enhanced computed tomography chest during evaluation of a child with recurrent cough.